Carbon-Based Catalyst from Pyrolysis of Waste Tire for Catalytic Ethanol Dehydration to Ethylene and Diethyl Ether. (5th February 2019) - Chaichana, Ekrachan; Wiwatthanodom, Weeraphat; Jongsomjit, Bunjerd
Abstract : This work investigated the use of waste tire as a source of carbon in preparation of carbon-based catalysts for applying in ethanol dehydration. The pyrolysis of waste tire was performed to obtain the solid carbon, and then it was treated with two different acids including HCl and HNO3 prior to the activation process with different temperatures to gain suitable carbon catalysts. All carbon catalysts were characterized using nitrogen physisorption, XRD, FTIR, and acid-base titration. The catalysts were tested for catalytic ethanol dehydration in a micropacked-bed reactor under the temperature range from 200°C to 400°C. It revealed that the ethanol conversion increased with increasing the reaction temperature for all catalysts. The carbon catalyst treated with HCl and calcined at 420°C (AC_H420) exhibited the highest ethanol conversion of 36.2% at 400°C having ethylene and diethyl ether selectivity of 65.9 and 33.5%, respectively. The high activity of this catalyst can be attributed to the high acid density at the surface (18.5  μ mol/m 2 ), which was significantly higher than those of most other catalysts (less than 8.0  μ mol/m 2 ).